Development of E-Modules with SSCS Model to Improve Students’ Critical Thinking Skills on Energy Crisis Materials - Farah Dhilah Balqis; Yayuk Mulyati; Arista, Rini Anggi; Nugraheni, Dian; Setiawan, Agung Mulyo (Universitas Tidar, 2025)
This research aims to develop and validate an e-module based on the Search, Solve, Create, and Share (SSCS) learning model to facilitate students' critical thinking skills on energy crisis materials. The research uses the ADDIE development model, which is limited to the formative evaluation stage, including needs analysis, design, development, and readability and practicality tests. The results of expert validation show that the e-module is in the